Functionalization of collagen fiber with nano-islands of silver via atomic layer deposition to promote bone healing - Astaneh, Sarah Hashemi; Faverani, Leonardo P. [UNESP]; Bhatia, Harshdeep; Dallazen, Eduardo [UNESP]; Costa, Monique Gonçalves [UNESP]; Ervolino, Edilson [UNESP]; Barão, Valentim A.R.; Sukotjo, Cortino; Takoudis, Christos G. (Elsevier, 2025)
Modern techniques of thin film deposition (e.g., atomic layer deposition [ALD]) have paved the way for the modification of the surface of target substrates with thin films, nanoparticles, or other types of nanomaterials. This novel way can improve the base material's properties and enhance specific properties through adding functionalized groups to the surface. In this study, ALD of silver was conducted on commercially available Type I collagen membrane to improve its bioactivity and promote bone healing. Two different sample groups were studied: pristine collagen and silver-coated collagen via ALD (Ag/Collagen). Chemical and morphological changes of the collagen membrane were investigated with X-ray photoelectron spectroscopy and scanning electron microscopy and the bioactivity of functionalized collagen with silver was studied in vitro and in vivo. Nano-islands of silver were obtained on collagen fibrils with an average diameter of ∼16 nm. Comparison of gingival cells cultured on pristine collagen, and silver-coated collagen, demonstrated that the attained silver nanoparticle size and concentration are below the toxicity level of silver. In vivo assessment in rat model showed the biocompatibility of the Ag/Collagen, and greater new bone formation compared to control. This novel solvent-free method can be used to functionalize sensitive materials used in surgeries as bone grafting agents to enhance osteopromotive properties without any adverse effects to the cellular environment.
Keywords: Atomic layer deposition; Bone healing; Collagen functionalization; Silver nano-islands